New records of rarely reported species in the Mediterranean Sea (March 2025) - JOSÉ CARLOS BÁEZ; OKAN AKYOL; ERNESTO AZZURRO; PIETRO BATTAGLIA; ANGEL BELMONTE-GALLEGOS; GEORGIOS CHRISTIDIS; FABIO CROCETTA; CEM DALYAN; YUNUS GÖNÜL; FABIO GRATI; SILVESTRO GRECO; CHRYSOULA GUBILI; et al. (Mediterranean Marine Science, 2025)
This collective study presents information on fifteen (15) species recorded across five countries (Greece, Italy, Slovenia, Spain, and Türkiye) and four (4) ecoregions, ranging from the Alboran Sea to the Aegean Sea. The recorded species belong to three phyla: Mollusca (3 species), Arthropoda (3 species), and Chordata (9 species). Among mollusks, Martadoris mediterranea is reported for the first time in the Aegean Sea at two different locations, while Opisthoteuthis calypso and Octopoteuthis sicula are newly recorded in the western Mediterranean. Regarding arthropods, Ocypode cursor is reported from the Tyrrhenian coast of Sicily, Pachygrapsus transversus is recorded for the first time in the Tyrrhenian Sea, and Cancer pagurus in the Sea of Marmara. Among chordates, Lobotes surinamensis and Zu cristatus are newly recorded in the Alboran Sea, while Callionymus fasciatus and Symphodus doderleini are reported from Slovenian coastal waters. Tripterygion delaisi and Gymnothorax unicolor are documented for the first time in the waters of the Sea of Marmara and Crete, respectively. Additionally, new records of rarely reported fish species include Arctozenus risso, Chromogobius zebratus, and Epinephelus aeneus in Turkish, Spanish, and Italian waters, respectively.

New records of rare species in the Mediterranean Sea (December 2022) - FEDERICA MONTESANTO; MARCO ALBANO; DΕΝΙΖ AYAS; FEDERICO BETTI; GIOELE CAPILLO; MELIH ERTAN ÇINAR; MARIA CORSINI-FOKA; FABIO CROCETTA; ERTAN DAĞLI; CLAUDIO D’IGLIO; MARKOS DIGENIS; BRANKO DRAGIČEVIĆ; et al. (Mediterranean Marine Science, 2022)
This Collective Article presents information on 20 taxa belonging to five (5) Phyla: Cnidaria (2), Mollusca (8), Arthropoda (4), Echinodermata (1) and Chordata (5) recorded from the Alboran Sea to the Levantine Sea. These new records were found in seven (7) different ecoregions as follows: Alboran Sea: new record of the rare football octopus Ocythoe tuberculata in the harbour of Algeciras (Spain); Western Mediterranean Sea: first record of the isopod Arcturinella deltensis in the Ligurian Sea, and the third in the whole Mediterranean Sea; third Mediterranean site for the Muricidae Coralliophila ahuiri along the Italian coasts (Alghero); first and westernmost record of the goby Corcyrogobius liechtensteini from the Iberian Peninsula; new record of the sea slug Glaucus atlanticus from the coast of the Iberian Peninsula; first and easternmost record of Holothuria (Vaneyothuria) lentiginosa lentiginosa along the Italian coasts; Tunisian Plateau/Gulf of Sidra: seventh record of the oceanic squid Thysanoteuthis rhombus in Tunisia, and first for the Gulf of Gabes. Ionian Sea: second occurrence of the Atlantic tripletail Lobotes surinamensis in the Ionian Sea and first record from the Strait of Messina area; new record of the rare sea elephant Pterotrachea coronata from the Strait of Messina; Adriatic Sea: first record of a facies of football ascidian Diazona violacea in the South Adriatic Sea (Tremiti Island, Italy); two records of the sevengill shark Heptranchias perlo in Croatian waters after more than 70 years of absence of documented records in this area; first known occurrence of the nudibranch Jalonus hyalinus in Slovenian waters and also the first known occurrence of this species in the Adriatic Sea; first record of the nudibranch Okenia elegans in Slovenian waters; Aegean Sea: First record of the parasitic isopod Nerocila milesensis along Greek coasts (Crete island) as well as the second record worldwide; additional record of the brachyuran Paragalene longicrura collected from the Saronikos Gulf (Greece); first record of the siphonophore Rhizophysa filiformis in Greek waters as well as the second record of this species in the eastern Mediterranean basin; new record of the rare and protected angelshark Squatina aculeata along Turkish coasts; Levantine Sea: first record of the marine amphipod Caprella andreae in the Levantine Mediterranean shore of Israel, based on both morphological and molecular data; first occurrence of the cephalopod Tremoctopus violaceus along Turkish coasts, which confirms its presence in the north-eastern coasts of Turkey; record of a bloom of the thermophilic jellyfish Pelagia noctiluca in the north Levantine Sea.

“New Mediterranean Biodiversity Records” (March 2017) - L. LIPEJ; I. ACEVEDO; E.H.K. AKEL; A. ANASTASOPOULOU; A. ANGELIDIS; E. AZZURRO; L. CASTRIOTA; M. ÇELIK; L. CILENTI; F. CROCETTA; A. DEIDUN; A. DOGRAMMATZI; et al. (Mediterranean Marine Science, 2017)
This Collective Article presents information on 22 species belonging to 5 Phyla, arranged geographically from from west to east. The new records were found in 8 countries as follows: Spain: first record of the two scarcely known nemerteans Baseodiscus delineatus and Notospermus geniculatus in Formentera; Malta: second record of the alien fish Lagocephalus sceleratus; Italy: the alien polychaete Syllis pectinans and the isopod Paranthura japonica, as well as the cryptogenic opisthobranch Anteaeolidiella lurana, were found in the fouling assemblages along the docks of the port of Livorno. New decapod records are reported from Sicily (the alien Callinectes sapidus and the native Pachygrapsus maurus) and Apulia (Percnon gibbosus and Procambarus clarkii); the lesser amberjack Seriola fasciata extended its geographical range to the Egadi Isands and Siganus luridus was documented for the first time along the Ionian coasts of Apulia and Calabria. Slovenia: the first record of the alien bivalve Brachidontes pharaonis is reported, together with a survey of up to date Adriatic records. Greece: the first record of the gastropod Rhinoclavis kochi is reported from Gavdos island. In addition, two records of endangered and rare cartilaginous fish were reported, namely, the shark Hexanchus griseus and the ray Leucoraja fullonica, as well as additional records of Siganus luridus for Lesvos and Malleus regula and Fulvia fragilis from Astypalaia. Turkey: the black wing flyingfish Hirundichthys rondeletii is reported for the very first time from the Black Sea. Egypt: the Indo-Pacific crab Halimede ochtodes is reported as established in Port Said. In addition, biometric parameters and meristic counts are reported for Anthias anthias in Damietta. Cyprus: the alien opisthobranch gastropod Bursatella leachii is reported for first time.

New Mediterranean Biodiversity Records (November, 2016) - CH. MYTILINEOU; E.H.Kh. AKEL; N. BABALI; P. BALISTRERI; M. BARICHE; Y.Ö. BOYACI; L. CILENTI; C. CONSTANTINOU; F. CROCETTA; M. ÇELİK; H. DERELI; C. DOUNAS; et al. (Mediterranean Marine Science, 2016)
In the present Collective Article information on 26 taxa belonging to 8 Phyla and extended from the western Mediterranean to the Levantine Sea are presented. The new records were found in 9 countries as follows: Spain: first record for the Mediterranean of the crab Cancer bellianus; Algeria: further records of the alien fish Lagocephalus sceleratus to the west Algerian waters; Italy: first report on the presence and establishment of the ctenophore Mnemiopsis leidyi in Lessina and Varano Lagoons (W. Adriatic) and of Penaeus aztecus in Corigliano Gulf (Italian Ionian). Moreover, the extension of the distribution range of the polychaete Branchiomma bairdi to W. Sicily as well as that of the crab Ocypode cursor and the bryozoan Catenicella paradoxa to E. Sicily are cited. Slovenia: the record of the rare saccoglossan gastropod Placida cremoniana from Piran (Gulf of Trieste) is the first for the Adriatic; Greece: the native sea slug Eubranchus farrani is the first from the Eastern Mediterranean; many sightings of the bamboo corals Isididae distributed along all the E. Ionian Sea and the establishment of P. aztecus in all Greek waters are also reported for first time; the westernmost extension of the alien urchin Diadema setosum in Cretan waters is cited and new sights of the alien species Goniobranchus annulatus and Pterois miles are shown. Turkey: the alien fish Champsodon capensis is reported for first time from the Aegean Sea and the native acari Agauopsis microrhyncha from the Levantine Sea; a new observation of the alien crab Atergatis roseus in Güllük Bay-Aegean is also mentioned; Cyprus: first records of the alien urchin D. setosum and Lobotes surinamensis in Cypriot waters; Lebanon: several sightings of Monachus monachus from the Lebanese waters indicate a potential better status of the species in the area, Egypt: first records of the alien crab Dorippe quadridens and the alien gastropods Nerita sanguinolenta and Conomurex persicus from the Mediterranean Egyptian waters; extension of the distribution range of Diodora funiculata and Diodora rueppellii and a second record of the alien Nerita sanguinolenta in the same area.

New Mediterranean Biodiversity Records (October 2015) - F. CROCETTA; D. AGIUS; P. BALISTRERI; M. BARICHE; Y.K. BAYHAN; M. ÇAKIR; S. CIRIACO; M. CORSINI-FOKA; A. DEIDUN; R. EL ZRELLI; D. ERGÜDEN; J. EVANS; et al. (Mediterranean Marine Science, 2015)
The Collective Article “New Mediterranean Biodiversity Records” of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided per countries, listed according to a Mediterranean west-east geographic position. New biodiversity data are reported for 7 different countries, although one species hereby reported from Malta is overall new for the entire Mediterranean basin, and is presumably present also in Israel and Lebanon (see below in Malta). Italy: the rare native fish Gobius kolombatovici is first reported from the Ionian Sea, whilst the alien jellyfish Rhopilema nomadica and the alien fish Oplegnathus fasciatus are first reported from the entire country. The presence of O. fasciatus from Trieste is concomitantly the first for the entire Adriatic Sea. Finally, the alien bivalve Arcuatula senhousia is hereby first reported from Campania (Tyrrhenian Sea). Tunisia: a bloom of the alien crab Portunus segnis is first reported from the Gulf of Gabes, from where it was considered as casual. Malta: the alien flatworm Maritigrella fuscopunctata is first recorded from the Mediterranean Sea on the basis of 25 specimens. At the same time, web researches held possible unpublished records from Israel and Lebanon. The alien crab P. segnis, already mentioned above, is first formally reported from Malta based on specimens collected in 1972. Concomitantly, the presence of Callinectes sapidus in Maltese waters is excluded since based on misidentifications. Greece: the Atlantic northern brown shrimp Penaeus atzecus, previously known from the Ionian Sea from sporadic records only, is now well established in Greek and international Ionian waters. The alien sea urchin Diadema setosum is reported from the second time from Greece, and its first record date from the country is backdated to 2010 in Rhodes Island. The alien lionfish Pterois miles is first reported from Greece and concomitantly from the entire Aegean Sea. Turkey: the alien rhodophyte Antithamnion hubbsii is first recorded from Turkey and the entire eastern Mediterranean. New distributional data are also offered for the native fishes Alectis alexandrina and Heptranchias perlo. In particular, the former record is constituted by a juvenile of 21.38 mm total length, whilst the latter by a mature male. Cyprus: the rare native cephalopod Macrotritopus defilippi, and the alien crab Atergatis roseus, sea slug Plocamopherus ocellatus and fish Cheilodipterus novemstriatus are first recorded from the entire country. Lebanon: the alien crabs Actaea savignii and Matuta victor, as well as the alien fish Synanceia verrucosa, are first recorded from the entire country. In addition, the first Mediterranean record of A. savignii is backdated to 2006, whilst the high number of M. victor specimens observed in Lebanon first suggest its establishment in the basin. The Atlantic fishes Paranthias furcifer and Seriola fasciata, and the circumtropical Rachycentron canadum, are also first reported from the country. P. furcifer record backdate its presence in the Mediterranean to 2007, whilst S. fasciata records backdate its presence in the eastern Mediterranean to 2005. Finally, two of these latter species have been recently ascribed to alien species, but all the three species may better fit the cryptogenic category, if not a new one.

New Mediterranean Biodiversity Records (July 2015) - K. TSIAMIS; Ö. AYDOGAN; N. BAILLY; P. BALISTRERI; M. BARICHE; S. CARDEN-NOAD; M. CORSINI-FOKA; F. CROCETTA; B. DAVIDOV; C. DIMITRIADIS; B. DRAGIČEVIĆ; M. DRAKULIĆ; et al. (Mediterranean Marine Science, 2015)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native species include: the neon flying squid Ommastrephes bartramii in Capri Island, Thyrrenian Sea; the bigeye thresher shark Alopias superciliosus in the Adriatic Sea; a juvenile basking shark Cetorhinus maximus caught off Piran (northern Adriatic); the deep-sea Messina rockfish Scorpaenodes arenai in the National Marine Park of Zakynthos (East Ionian Sea, Greece); and the oceanic puffer Lagocephalus lagocephalus in the Adriatic Sea.The new records of alien species include: the red algae Antithamnionella elegans and Palisada maris-rubri, found for the first time in Israel and Greece respectively; the green alga Codium parvulum reported from Turkey (Aegean Sea); the first record of the alien sea urchin Diadema setosum in Greece; the nudibranch Goniobranchus annulatus reported from South-Eastern Aegean Sea (Greece); the opisthobranch Melibe viridis found in Lebanon; the new records of the blue spotted cornetfish Fistularia commersonii in the Alicante coast (Eastern Spain); the alien fish Siganus luridus and Siganus rivulatus in Lipsi Island, Dodecanese (Greece); the first record of Stephanolepis diaspros from the Egadi Islands Marine Protected Area (western Sicily); a northward expansion of the alien pufferfish Torquigener flavimaculosus along the southeastern Aegean coasts of Turkey; and data on the occurrence of the Lessepsian immigrants Alepes djedaba, Lagocephalus sceleratus and Fistularia commersonii in Zakynthos Island (SE Ionian Sea, Greece).

New insights on the biological parameters of the exploited cuttlefish Sepia officinalis L. (Mollusca: Cephalopoda) in the northern Adriatic Sea in relation to the main fishing gears employed - N. BETTOSO; D. BORME; L. FARESI; I. ALEFFI; M. ORLANDO-BONACA; L. LIPEJ (Mediterranean Marine Science, 2015)
The cuttlefish (Sepia officinalis Linnaeus 1758) represents one of the most important coastal fishery resources of the Mediterranean Sea. For Italy, 45% of cuttlefish landings (2,328 t) originates from coastal regions of the northern Adriatic Sea: Veneto, Marche, Emilia Romagna and Friuli Venezia Giulia. In terms of economic value this species represents about 8% (~€ 16.5 million) of the production from this basin. From May 2004 to October 2005, cuttlefish were purchased from commercial landings of the Grado fishery fleet. At least 30 specimens were randomly taken each month from each fishing method employed for this species: bottom trawl (cod end mesh size 40 mm), rapido trawl, trammel net (mesh size of inner panel 30 mm) and cuttlefish specific trap. The main biological aspects, such as size, sex ratio, reproductive stage and diet in relation to both the season and type of fishing gear were analyzed. 1,495 specimens, ranging from 3.5 to 18.0 cm mantle length, were analyzed. In relation to the observed size and reproductive stage of individuals caught, trammel nets and cuttlefish traps both appeared to target sexually mature individuals, whilst trawling gear were not selective for either recruits or spawners. In total 34 prey taxa were found in the stomachs of S. officinalis: crabs and bony fish species were the most important prey, although the latter appeared mostly in the largest specimens. Finally the fullness index revealed that cuttlefish caught by trawling were more suitable for diet analysis than those caught by static gear. In this way the contribution of the present paper was to give new insights on the biological parameters of this species in relation to the main fishing gears employed in the northern Adriatic Sea.

New Mediterranean Biodiversity Records (April 2015) - Α. ΖΕΝΕΤΟΣ; E.H.KH. AKEL; C. APOSTOLIDIS; M. BILECENOGLU; G. BITAR; V. BUCHET; N. CHALARI; M. CORSINI-FOKA; F. CROCETTA; A. DOGRAMMATZI; M. DRAKULIĆ; G. FANELLI; et al. (Mediterranean Marine Science, 2015)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native fish species include: the slender sunfish Ranzania laevis and the scalloped ribbonfish Zu cristatus in Calabria; the Azores rockling Gaidropsarus granti in Calabria and Sicily; the agujon needlefish Tylosurus acus imperialis in the Northern Aegean; and the amphibious behaviour of Gouania willdenowi in Southern Turkey. As regards molluscs, the interesting findings include Ischnochiton usticensis in Calabria and Thordisa filix in the bay of Piran (Slovenia). The stomatopod Parasquilla ferussaci was collected from Lesvos island (Greece); the isopod Anilocra frontalis was observed parasitizing the alien Pteragogus trispilus in the Rhodes area. The asteroid Tethyaster subinermis and the butterfly ray Gymnura altavela were reported from several localities in the Greek Ionian and Aegean Seas. The new records of alien species include: the antenna codlet Bregmaceros atlanticus in Saronikos Gulf; three new fish records and two decapods from Egypt; the establishment of the two spot cardinal fish Cheilodipterus novemstriatus and the first record of the Indo-Pacific marble shrimp Saron marmoratus in semi-dark caves along the Lebanese coastline; the finding of Lagocephalus sceleratus, Sargocentron rubrum, Fistularia commersonii and Stephanolepis diaspros around Lipsi island (Aegean Sea, Greece); the decapod Penaeus hathor in Aegean waters; the decapod Penaeus aztecus and the nudibranch Melibe viridis in the Dodecanese islands; the finding of Pinctada imbricata radiata in the Mar Grande of Taranto (Ionian Sea, Italy) and the Maliakos Gulf (Greece).

Mollusc fauna associated with the Cystoseira algal associations in the Gulf of Trieste (Northern Adriatic Sea) - V. PITACCO; M. ORLANDO-BONACA; B. MAVRIČ; A. POPOVIĆ; L. LIPEJ (Mediterranean Marine Science, 2014)
Mollusc assemblages associated with Cystoseira associations were sampled in the southern part of the Gulf of Trieste during the summers of 2008 and 2012. Samples were collected by SCUBA diving in the infralittoral belt (from 1 to 4 m depth). The surface within frames of 20 x 20 cm was scraped off with samples were collected by hand or with an air-lift sampler. Four erected algal species were found: Cystoseira barbata, C. compressa, C. corniculata and Halopithys incurva. A total of 69 species of molluscs were identified in those associations. Gastropoda were dominant, with the highest species richness and abundance, followed by Bivalvia and Polyplacophora. A large number of juveniles were found, proving the importance of Cystoseira associations for mollusc recruitment. Differences in composition, structure and abundance of mollusc assemblages were found for sites dominated by different algal species, and correspond to different morphology and degree of development of canopy-forming species. The present study confirms that the dominant algal species within Cystoseira associations strongly influence, although at different levels, abundance and distribution of mollusc assemblages in the Northern Adriatic Sea.

New Mediterranean Biodiversity Records (April, 2014) - K. KAPIRIS; C. APOSTOLIDIS; R. BALDACCONI; N. BAŞUSTA; M. BILECENOGLU; G. BITAR; D.C. BOBORI; Y.Ö BOYACI; C. DIMITRIADIS; M. DJUROVIĆ; J. DULČIĆ; F. DURUCAN; et al. (Mediterranean Marine Science, 2014)
According to reports, the following 16 species have extended their distribution to other Mediterranean areas or have made a new appearance in other regions. The first category includes the following organisms: The rare and common Indo-Pacific seaweed Codium arabicum (Lebanese coasts), the acari Thalassarachna affinis (Marmara Sea), and the non-indigenous nudibranch Flabellina rubrolineata, which has also been found in many other areas of the Aegean Sea. In addition, the rare sea slug Thecacera pennigera (Piccolo of Taranto), the fangtooth moray Enchelycore anatina (National Marine Park of Zakynthos, Ionian Sea), the carangid Seriola fasciata (Gulf of Antalya), Lagocephalus sceleratus (SE. Ionian Sea), the reticulated leatherjacket Stephanolepis diaspros (Slovenia, N. Adriatic Sea), the marbled stingray, Dasyatis marmorata (NE Levantine), the starry smooth-hound Mustelus asterias (Iskenderun Bay, NE Mediterranean), the cephalopod Ommastrephes bartramii (Ionian Sea) have also been reported. The Atlantic crab Dyspanopeus sayi has expanded to many Italian areas and the blue crab Callinectes sapidus to a lake in N. Greece and in the S. Adriatic Sea. Finally, Farfantepenaeus aztecus has been found in the Ionian Sea, thus showing its wide expansion in the Mediterranean. The larval stages of Faccionella oxyrhyncha have been found, after many years, in the Aegean Sea and the first report of an existence on intersexual acari Litarachna duboscqi in Split(Adriatic Sea) was reported.

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways - Α. ZENETOS; S. GOFAS; C. MORRI; A. ROSSO; D. VIOLANTI; J.E. GARCIA RASO; M.E. CINAR; A. ALMOGI-LABIN; A.S. ATES; E. AZZURRO; E. BALLESTEROS; C.N. BIANCHI; et al. (Mediterranean Marine Science, 2012)
More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 species per year for macrophytes, molluscs and polychaetes, 3-4 species per year for crustaceans, and 6 species per year for fish. The dominant group among alien species is molluscs (with 215 species), followed by crustaceans (159) and polychaetes (132). Macrophytes are the leading group of NIS in the ADRIA and the WMED, reaching 26-30% of all aliens, whereas in the EMED they barely constitute 10% of the introductions. In the EMED, molluscs are the most species-rich group, followed by crustaceans, fish and polychaetes. More than half (54%) of the marine alien species in the Mediterranean were probably introduced by corridors (mainly Suez). Shipping is blamed directly for the introduction of only 12 species, whereas it is assumed to be the most likely pathway of introduction (via ballasts or fouling) of another 300 species. For approximately 100 species shipping is a probable pathway along with the Suez Canal and/or aquaculture. Approximately 20 species have been introduced with certainty via aquaculture, while >50 species (mostly macroalgae), occurring in the vicinity of oyster farms, are assumed to be introduced accidentally as contaminants of imported species. A total of 18 species are assumed to have been introduced by the aquarium trade. Lessepsian species decline westwards, while the reverse pattern is evident for ship-mediated species and for those introduced with aquaculture. There is an increasing trend in new introductions via the Suez Canal and via shipping.

State of the Art of the Marine Non-Indigenous Flora and Fauna in Slovenia - L. LIPEJ; B. MAVRIC; M. ORLANDO-BONACA; A. MALEJ (Mediterranean Marine Science, 2012)
Authors provide the state of knowledge on marine non-indigenous species in waters off Slovenia. According to published records and authors unpublished data at least 15 non-indigenous species were up to date recorded in the Slovenian part of the Adriatic sea. Eleven species were considered as established and four species as casual. The vectors of introduction are various, comprising Lessepsian migration, mariculture and shipping. The majority of non-indigenous taxa were recorded in the mediolittoral belt and coastal lagoons. The low number of non-indigenous species so far recorded in the Slovenian part of the Adriatic sea could be explained by various factors. Among them, the most reasonable are the lack of scientific attention, the small proportion of Slovenian Sea and low winter temperatures, which represents a physiological barrier for the survival of newcomers. The number of recorded species is far from being satisfactory. Therefore, we expect that the list of non-indigenous species will be enlarged in the nearby future.

The largescaled terapon Terapon theraps : a new Indo‐Pacific fish in the Mediterranean Sea - L. Lipej; B. Mavrič; V. ŽIža; J. Dulčić (Journal of Fish Biology, 2008)
A specimen of the largescaled terapon Terapon theraps was recorded for the first time from the Mediterranean Sea. The finding of T. theraps in the northernmost part of the Mediterranean Sea raises the number of Lessepsian migrant species to at least 68 and in the Adriatic Sea to at least 11.